1994
DOI: 10.3109/00016349409006269
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to drug consumption during pregnancy

Abstract: A survey on drug intake during pregnancy was carried out in a sample of 3268 women who delivered live-born infants in 11 hospitals located throughout Italy. A large questionnaire on drug use and other aspects of maternal life-style was administered within five days of delivery to 3112 women who consented to the interview. An overall mean consumption of 2.17 drugs per woman was reported. Apart from dietary supplements, the most used drugs were tocolytics, analgesics, and antibiotics. The proportion of women who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
2
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 14 publications
(4 reference statements)
1
21
2
5
Order By: Relevance
“…Some have been based on institutional databases 8,12,13,23,27,29,37 and have therefore considered only the prescribed vitamins/minerals, not reflecting the real intake. When information was obtained by interview, the moment of data collection was different and varied from prenatal visits 1,7,10,15,16,17,18,19,21,22,25,26,31,34,35,36,38,44,45 until two months after childbirth 9,11,14,20,24,30,33,46,47 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some have been based on institutional databases 8,12,13,23,27,29,37 and have therefore considered only the prescribed vitamins/minerals, not reflecting the real intake. When information was obtained by interview, the moment of data collection was different and varied from prenatal visits 1,7,10,15,16,17,18,19,21,22,25,26,31,34,35,36,38,44,45 until two months after childbirth 9,11,14,20,24,30,33,46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have quantified the use of vitamins and minerals in pregnancy 1,4,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38 , and some have addressed its association with age 11,12,13,30,31,38 , ethnicity 8,12,13,30,33 , education 11,13,18,30,31,36,38 , marital status …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os estudos sobre a prevalência do uso de medicamentos na gravidez se intensificaram nas últimas duas décadas 3,4,5,6,7 e apontam que, em vários países, mais de 80% das mulheres utilizam algum tipo de medicamento durante a gestação 8,9 .…”
Section: Introductionunclassified
“…Additionally, infections of the reproductive and urinary tracts, sexually transmitted diseases, systemic infections have all been linked to birth outcomes through various immune-mediating processes, compromised by the experiences of stress during pregnancy (Coussons-Read et al, 2012;D'Anna-Hernandez et al, 2012). Lastly, it has been suggested that the behavioural pathways to adverse birth outcomes may consist of unhealthy lifestyle factors during pregnancy, such as smoking, substance use, and poor nutrition (Bakker et al, 2011;Barros, Mitsuhiro, Chalem, Laranjeira, & Guinsburg, 2011;Bonassi et al, 1994;Kramer & McDonald, 2009). A general consensus amongst these hypotheses is that there is a very limited understanding about how these mechanisms work (Dunkel-Schetter, 2011).…”
Section: Overviewmentioning
confidence: 99%